Collagen changes in the cochlea of aged Fischer 344 rats - Buckiova, Daniela; Popelar, Jiri; Syka, Josef (Experimental gerontology, 2006)
Hearing function in the Fischer 344 (F344) albino inbred strain of rats deteriorates with aging faster than in other strains, in spite of the small hair cell loss in old F344 animals [Popelar, J., Groh, D., Pelanova, J., Canlon, B., Syka, J., 2005. Age-related changes in cochlear and brainstem auditory function. Neurobiol. Aging, in press.]. This study was aimed at elucidating the structural changes in the inner ear of this rat strain during aging. Cochlear histopathology was examined in 20-24-month-old F344 rats and compared with that of young F344 rats (4 months) and of old rats of the Long-Evans (LE) strain. Hematoxylin/eosin staining in aged F344 rats showed degenerative changes in the organ of Corti, consisting of a damaged layer of marginal cells, reduced vascularization of the stria vascularis and a distorted tectorial membrane detached from the organ of Corti. Age-related changes in collagen distribution were observed with Masson's trichrome staining in the spiral ligament of old F344 rats. The results of immunohistochemical staining for type II collagen revealed a marked decrease in collagen fibers in the area connecting the spiral ligament and stria vascularis and a decrease in area IV fibrocytes in old F344 but not in LE rats. These findings may contribute to an explanation of the substantial hearing loss found in old F344 rats.
Keywords: kolagen typ II; Hematoxylin; membrana tectoria; potkani inbrední F344; barvicí látky; stria vascularis; Methyl Green; Coloring Agents; Stria Vascularis; zvířata; Rats; Tectorial Membrane; Collagen Type II; kochlea; imunohistochemie; methylová zeleň; Fluorescent Dyes; Immunohistochemistry; Eosine Yellowish-(YS); Cortiho orgán; Aging; eosin; Collagen; kolagen; Cochlea; Rats, Inbred F344; krysa rodu Rattus; Animals; fluorescenční barviva; Organ of Corti; Azo Compounds; hematoxylin; azosloučeniny; stárnutí